New Chloramphenicol Derivatives from the Viewpoint of Anticancer and Antimicrobial Activity - Giannopoulou, Panagiota C. (Antibiotics (Basel), 2019)
Over the last years, we have been focused on chloramphenicol conjugates that combine in their structure chloramphenicol base with natural polyamines, spermine, spermidine and putrescine, and their modifications. Conjugate 3, with spermidine (SPD) as a natural polyamine linked to chloramphenicol base, showed the best antibacterial and anticancer properties. Using 3 as a prototype, we here explored the influence of the antibacterial and anticancer activity of additional benzyl groups on N1 amino moiety together with modifications of the alkyl length of the aminobutyl fragment of SPD. Our data demonstrate that the novel modifications did not further improve the antibacterial activity of the prototype. However, one of the novel conjugates (4) showed anticancer activity without affecting bacterial growth, thus emerging as a promising anticancer agent, with no adverse effects on bacterial microflora when taken orally.